2017
DOI: 10.1111/ecog.02649
|View full text |Cite
|
Sign up to set email alerts
|

Time and environment explain the current richness distribution of non‐marine turtles worldwide

Abstract: Ecological, historical, and evolutionary hypotheses are important to explain geographical diversity gradients in many clades, but few studies have combined them into a single analysis allowing a comparison of their relative importance. This study aimed to evaluate the relative importance of ecological, historical, and evolutionary hypotheses in explaining the current global distribution of non-marine turtles, a group whose distribution patterns are still poorly explored. We used data from distribution range ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…Terrestrial turtles were mainly characterized by mesic niches (scores close to zero). Such mesic niches (and a lower richness when compared to aquatic turtles) help to explain why richness and biogeographic patterns of turtles as a whole are also strongly related to precipitation and thus similar to the patterns of aquatic species alone (Ennen, Agha, Matamoros, Hazzard, & Lovich, ; Ennen et al., ; Iverson, ; Rodrigues et al., ). Finally, previous studies have found that the ancestor of recent turtles was most likely aquatic (Jaffe et al., ; Joyce & Gauthier, ; Rodrigues & Diniz‐Filho, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Terrestrial turtles were mainly characterized by mesic niches (scores close to zero). Such mesic niches (and a lower richness when compared to aquatic turtles) help to explain why richness and biogeographic patterns of turtles as a whole are also strongly related to precipitation and thus similar to the patterns of aquatic species alone (Ennen, Agha, Matamoros, Hazzard, & Lovich, ; Ennen et al., ; Iverson, ; Rodrigues et al., ). Finally, previous studies have found that the ancestor of recent turtles was most likely aquatic (Jaffe et al., ; Joyce & Gauthier, ; Rodrigues & Diniz‐Filho, ).…”
Section: Discussionmentioning
confidence: 97%
“…We note that using temperature data from terrestrial conditions to describe species' aquatic niches may seem controversial, but recent studies have shown that water temperatures are highly correlated with terrestrial ones at the scale of species geographic distributions (Frederico, De Marco, & Zuanon, ; Livingstone & Lotter, ). In fact, several recent studies evaluating climatic niche and distribution patterns of aquatic organisms, such as fishes (Culumber & Tobler, ; Edeline, Lacroix, Delire, Poulet, & Legendre, ; Emmrich et al., ) and turtles (Fagundes, Vogt, & De Marco Júnior, ; Ihlow et al., ; Rödder et al., ; Rodrigues, Olalla‐Tárraga, Iverson, Akre, & Diniz‐Filho, ; Waterson et al., ), have been performed using data on terrestrial conditions. Furthermore, it is important to highlight that even aquatic turtles also depend on terrestrial environments for activities such as basking and nesting, which are in turn environmentally influenced, reinforcing the relevance of terrestrial environmental conditions on their niches.…”
Section: Methodsmentioning
confidence: 99%
“…We did not use a larger threshold because turtle richness is generally low, and higher thresholds would dramatically reduce our sample number (see Rodrigues et al . () and table S1.3 for general information regarding turtle richness in global and biogeographical scale).…”
Section: Methodsmentioning
confidence: 99%
“…Cells encompassing communities phylogenetically clustered (SES values lower than −1.96) were mainly found in areas of high turtle species richness (Buhlmann et al., ; Rodrigues et al., ). This similarity is stronger for SESMNTD values, which describe the relationships for the most recently divergent species (i.e.…”
Section: Discussionmentioning
confidence: 99%